Analisis Pengaruh Brand Image dan Harga terhadap Keputusan Pembelian Konsumen (Studi pada Produk Fashion Online) - Mandasari, Puti; Machmud, Pajar (JIMAD : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of brand image and price on consumer purchasing decisions for online fashion products. The research method used a quantitative approach with a survey technique through the distribution of questionnaires to 120 respondents who had purchased fashion products through e-commerce platforms. Data analysis was performed using multiple linear regression using SPSS software. The results show that brand image has a positive and significant effect on consumer purchasing decisions, while price also has a positive but lower influence than brand image. The combination of the two explains 62.4% of the purchasing decision variable. This study emphasizes the importance of company strategies in building a strong brand image and setting competitive prices to increase consumer purchasing interest in the online fashion market.